Editorial - Osmani, Noor Mohammad (IIUM Press, 2025)
It is with great pleasure that we present to our esteemed readers the August 2025 issue of al-Burhān: Journal of Qur’an and Sunnah Studies. This volume brings together a diverse range of scholarly contributions that engage with the Qur’an, the Prophetic Sunnah, Islamic thought, and the lived realities of Muslim societies. Collectively, the articles reflect a balance between classical textual scholarship and contemporary socio-intellectual challenges, reaffirming the dynamism of Islamic knowledge in addressing perennial questions and modern predicaments.